Avaliação do retinol em parturientes com diabetes mellitus gestacional no pós parto imediato - Resende, Fernanda Barros Soares (2013)
Micronutrient deficiencies affect individuals mainly in developing countries, where vitamin A deficiency is a public health problem worldwide more worrying, especially in groups with increased physiological needs such as children and women of reproductive age. Vitamin A is supplied to the body through diet and has an important role in the visual process, cell differentiation, maintenance of epithelial tissue, reproductive and resistance to infection. The literature has demonstrated the relationship between vitamin A and diabetes, including gestational, leading to a risk to both mother and child. Gestational diabetes is any decrease in glucose tolerance of variable magnitude diagnosed each the first time during pregnancy, and may or may not persist after delivery. Insulin resistance during pregnancy is associated with placental hormones, as well as excess fat. Studies have shown that retinol transport protein produced in adipose tissue in high concentrations, this would be associated with resistance by interfering with insulin signaling. Therefore, this study aimed to evaluate the concentration of retinol in serum and colostrum from healthy and diabetic mothers in the immediate postpartum period. One hundred and nine parturient women were recruited, representing seventy-three healthy and thirty-six diabetic. Retinol was extracted and subsequently analyzed by High Performance Liquid Chromatography. Among the results highlights the mothers with gestational diabetes were older than mothers healthy, had more children and a higher prevalence of cases of cesarean section. Fetal macrosomia was present in 1.4% of healthy parturient women and in 22.2% of diabetic mothers. The maternal serum retinol showed an average of 39.7 ± 12.5 mg/dL for healthy parturients 35.12 ± 15 mg/dL for diabetic and showed no statistical difference. It was observed that in the group of diabetic had 17% vitamin A deficiency, whereas in the healthy group, only 4% of the women were deficentes. Colostrum, the concentration of retinol in healthy was 131.3 ± 56.2 mg/dL and 125.3 ± 41.9 mg/dL in diabetic did not differ statistically. This concentration of retinol found in colostrum provides approximately 656.5 mg/day for infants born to healthy mothers and 626.5 mg/day for infants of diabetic mothers, based on a daily consumption of 500 mL of breast milk and need Vitamin A 400 mg/day, thus reaching the requirement of the infant. The diabetic mothers showed significant risk factors and complications related to gestational diabetes. Although no 11 difference was found in serum retinol concentration and colostrum among women with and without gestational diabetes, the individual analysis shows that parturients women with diabetes are 4.9 times more likely to develop vitamin A deficiency than healthy parturients. However, the supply of vitamin A to the newborn was not committed in the presence of gestational diabetes